Enteroviruses and Adenoviruses in stool specimens of paralytic children- can they be the cause of paralysis? - Yousefi, Maryam (Iran J Microbiol, 2018)
BACKGROUND AND OBJECTIVES: Acute flaccid paralysis (AFP) is a complicated clinical syndrome with a wide range of potential etiologies. Several infectious agents including different virus families have been isolated from AFP cases. In most surveys, Non-polio Enteroviruses (NPEVs) have been detected as main infectious agents in AFP cases; however, there are also some reports about Adenovirus isolation in these patients. In this study, NPEVs and Adenoviruses in stool specimens of AFP cases with or without Residual Paralysis (RP) with negative results for poliovirus are investigated. MATERIALS AND METHODS: Nucleic acid extractions from 55 AFP cases were examined by nested PCR or semi-nested PCR with specific primers to identify NPEVs or Adenoviruses, respectively. VP1 (for Enteroviruses) and hexon (for Adenoviruses) gene amplification products were sequenced and compared with available sequences in the GenBank. RESULTS: From 55 fecal (37 RP+ and 18 RP−) specimens, 7 NPEVs (12.7%) (2 cases in RP+) and 7 Adenoviruses (12.7%) (4 cases in RP+) were identified. Echovirus types 3, 17 and 30, Coxsackie virus A8, and Enterovirus 80 were among NPEVs and Adenoviruses type 2 and 41 were also identified. CONCLUSION: Our finding shows that NPEVs and Adenoviruses may be isolated from the acute flaccid paralyses but there is no association between the residual paralyses and virus detection.